2012
DOI: 10.21608/eajbsa.2012.14797
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of certain biopesticides against the olive black scale insect,Saissetia oleae (Olivier) on olive trees at Giza Governorate, Egypt

Abstract: An experiment was carried out to investigate the effect of some biopesticides for controlling the olive black scale insect, Saissetia oleae (Olivier) on olive trees at Giza Governorate, Egypt during April, 2010. Four biopesticides (Biover, Stanes-biocatch, Stanes-biomagic and Bioranza) and one plant extract (Nimbecidine) were tested. The obtained results showed that all tested biopesticides and one extract were able to decrease the infestation with the olive black scale insect on olive trees through the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Impact of chemical and safe alternative compounds on olive pests and their associated natural enemies has been studied by several investigators e.g. ; Eid and Wafaa (2008); Moustafa et al (2009); Youssef et al (2011);Ibraheem et al (2012); Ammar et al (2013); Sabbour (2013); Hegazi (2013) and Amin et al (2013b).…”
Section: Toxicological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Impact of chemical and safe alternative compounds on olive pests and their associated natural enemies has been studied by several investigators e.g. ; Eid and Wafaa (2008); Moustafa et al (2009); Youssef et al (2011);Ibraheem et al (2012); Ammar et al (2013); Sabbour (2013); Hegazi (2013) and Amin et al (2013b).…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…They suggested that the post spraying count must be continue 4 weeks after application to determine the efficacy of the evaluated insecticides for control their insect pest. Concerning the alternative compounds, an experiment was carried out by Ibraheem et al (2012) to investigate the effect of some bio pesticides for controlling the olive black scale insect Saissetia oleae on olive trees at Giza Governorate. Four biopesticides (Biovar, Stanes-biocatch, Stanes-biomagic and Bioranza) and one plant extract (Nimbecidine) were tested.…”
Section: Toxicological Studiesmentioning
confidence: 99%
See 1 more Smart Citation